PERSPEKTIF BANSER-NU TENTANG TOLERANSI KERAGAMAN AGAMA DALAM PERISTIWA BOM NATAL 2000 - Imam Sujono (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2021)
In the Qur’an there is Surat Al-Kafirun verse 6,which reads “lakum diinukum wa liyadiin,” whichmeans “For you your religion, and for me my religion.” In this letter it is sufficient to show how tolerance is in religion. This reflects how to respect the belief rights of fellow humans. Not imposing one’s will, not compelling someone to embrace a certain religion, not discrediting other religions, and respecting to practice their religion and belief. The research titled “ BANSER-NU Perspective on the Tolerance of Religious Diversity Concerning the Incident of Christmas Bombing 2000” focus on (1) How is the relationship between harmony and religious diversity tolerance? (2) What are the views of Nahdlatul Ulama and BANSER for religious diversity tolerance? (3) How did BANSER Riyanto die when securing Christmas celebrations? This research uses field research and literature review with historical sociology approaches. From the research results, obtaines the following answers: (1) Tolerance of religious diversity has an important in realizing plural community harmony in the life of the nation and state (2) BANSER is part of NU, both of which understand Ahlussunnah Wal Jamaah and there is tasamuh who are seen as Ukhuwah Insaniyah (humanity) and Ukhuwah Wathaniyah (nationalism) which are the basic principles of tolerance for religious diversity, so that NU and BANSER always try to create, maintain tolerance for religious diversity (3) BANSER Riyanto is safeguarding the 2000 Christmas celebration at Eben Haezar Church in Mojokerto, and died with a bomb explosion to save the Christmas congregation.